The effects of nurse-delivered caregiving in the neonatal setting: An integrative review. Issue 5 (October 2021) - Griffiths, Nadine; Laing, Sharon; Spence, Kaye; Foureur, Maralyn; Sinclair, Lynn
Abstract: Infants hospitalised in neonatal intensive care units require interventions for lifesaving care and to meet basic human needs. Evidence that stress influences neurodevelopment suggests the effects of caregiving in the neonatal intensive care unit (NICU) warrant further investigation to assess links with infant developmental outcomes. This review explores the effects of nurse-delivered caregiving in the NICU on infant physiological and behavioural responses, and longer-term developmental outcomes (behaviour and temperament). CINHAL, MEDLINE and PsychINFO were systematically searched for studies in peer-reviewed journals related to nurse-delivered caregiving and developmental outcomes. Synthesis of the literature identified altered physiological and behavioural responses as immediate effects of caregiving in neonatal settings, and non-optimal developmental outcomes. Results indicate that caregiving is not innocuous. Yet, little is known about nurses' perceptions of the effects of caregiving. Identifying the care components that influence development is essential to minimise the potentially adverse impact of the NICU experience on infants and families.